Analisis Penggunaan Bahasa Sasak-Bahasa Indonesia Pada Pembelajaran Keterampilan Berbicara Siswa - Hadi, Yusnan; Padlurrahman, Padlurrahman; Mashun, Mashun (Educatio, 2024)
School is one of the formal educational institutions that are also inseparable from learning activities.Formal education institutions have institutional goals that are broken down in various substances, especially in learning materials related to the ability to speak in children. Speaking skills are something that must be owned by students so as not to vacuum in a discussion so as to be able to express ideas or ideas. The social environment of the community is very influential on the ability of children in the mastery or use of the Indonesian language properly and correctly. It is not uncommon to find a number of children who are less able or even unable to use Indonesian to express their hearts or ideas during teaching and learning activities. The strong influence of sasak language is very influential on the ability of children to speak Indonesian. The lack of Indonesian vocabulary is one of the problems that arise due to the lack of use of Indonesian in their surroundings. The use of sasak language which is very dominant both at home and at school is a major factor in the lack of ability of children to speak Indonesian.